0796 Does In-Situ High Fidelity Simulation and Education Improve the Comfort Levels of Sleep Technologists Responding to Medical Emergencies in a Pediatric Sleep Center. (12th April 2019) - Langston, Blair; Spray, Beverly; Spence, Jacki; Hungerford, James
Abstract: Introduction: This sleep lab is located within a free standing pediatric hospital serving patients from infancy to 18 years of age. It is currently accredited through the American Academy of Sleep Medicine (AASM). In 2016, the AASM changed the emergency drill criteria to include annual drills performed on the unit. Few studies have been conducted to identify the best method to prepare sleep technologists (ST) to respond in emergent situations. Although these events are rare, the risk remains high. A program was developed utilizing the Medical Emergency Team (MET) and Simulation specialist. The criteria was aimed at enhancing the ST ability to recognize deteriorating patients and increase comfort levels when responding to emergent situations. Methods: The participants were required to recognize signs of deterioration and respond appropriately to these events. Participants responded to an in-situ mock code scenario utilizing high fidelity simulation mannequins. These were conducted in the sleep lab and required participants to use available emergency equipment. Each session began with a pre-survey and introduction to the team and mannequin. Each ended with debriefing, education, post-survey, and evaluations. Wilcoxon signed-ranks tests were used to test for pre to post differences in survey items. The Holm-Bonferroni procedure was used to correct for multiple testing. Results: A total of 14 staff members participated (1-Registered Nurse, 4-Respiratory Therapist, and 9 Sleep Technologist).The response rate for pre and post surveys was 100%. On average, respondents felt significantly more comfortable with their skills needed to perform basic life support and the ability to identify their role when a code team arrived. Additionally, education increased the comfort level of respondents when identifying signs and symptoms of sepsis and troubleshooting equipment. Conclusion: A unit specific, in-situ mock code simulation may increase the ST ability to recognize deteriorating patient and increase their comfort levels when responding to potential high risk situations. Support (If Any)